2011
DOI: 10.4028/www.scientific.net/msf.684.177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Pinning, Locking and Adaption of Twins on the Performance of Magnetic Shape-Memory Alloys

Abstract: We study the effect of surface modifications and constraints on the mechanical properties of Ni-Mn- Ga single crystals, which are imposed by (i) structural modifications near the surface, (ii) mounting to a solid surface, and (iii) guiding the stroke. Spark eroded samples were electropolished and characterized before and after each polishing treatment. Surface damage was then produced with spark erosion and abrasive wearing. Surface damage stabilizes and pins a dense twin-microstructure and prevents twins from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…The superelastic stress-strain curves in Fig.3a, 3b and 3c show serrated response, which is more pronounced during the forward transformation. Similar serrated stress strain behaviors were observed previously in other FeMnAlNi alloys as well as in magnetic SMAs such as NiMnGa [24,25]. Omori et al reported serrated stress-strain behavior in FeMnAlNi polycrystalline wires with a d/D ratio greater than one [19].…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The superelastic stress-strain curves in Fig.3a, 3b and 3c show serrated response, which is more pronounced during the forward transformation. Similar serrated stress strain behaviors were observed previously in other FeMnAlNi alloys as well as in magnetic SMAs such as NiMnGa [24,25]. Omori et al reported serrated stress-strain behavior in FeMnAlNi polycrystalline wires with a d/D ratio greater than one [19].…”
supporting
confidence: 79%
“…Serrated deformation behavior has also been observed in NiMnGa [24,25], however the serrations were linked to the surface roughness of the samples. The damaged surface layer resulting from spark plasma cutting or introduced via surface preparation can become stress concentrators, act as finely dispersed pinning sites for twin boundaries, and limits the ability of the martensite to coarsen.…”
mentioning
confidence: 88%
“…When defects such as scratches are below 10 nm, the average switching field (and hence twinning stress) is lowered and twin nucleation occurs more easily [27]. When surface defects are much larger there is a tendency for dislocations to become pinned and interact with other passing dislocations [18,26]. Polishing with coarse slurry leads to a rougher surface and a stressed surface layer which allows for increased number of crack initiation points where dislocations will pile up and induce high stress concentration points.…”
Section: Single Crystalmentioning
confidence: 97%
“…Constraining the FSMA element inhibits twin reorientation locally within the constrained volume. Surface defects and residual stresses limit twin boundary motion and increases twinning stress [18]. Constrained samples exhibit reduced strain and prolonged fatigue life [19].…”
Section: Introductionmentioning
confidence: 99%
“…Surface damage stabilizes a fine twin structure, as shown by Chmielus et al [79] and Ezer et al [80]. 10M samples with fine twin structure, whether oriented or lamellar, exhibits good fatigue life [71,83]. In [76], Straka et al propose a phenomenological model, which describes the mechanism of reducing fatigue.…”
Section: Effect Of Surface Properties and Constraintsmentioning
confidence: 99%